Programas de conservación de fauna en Colombia: Perspectivas en el país megadiverso (2017)
The accelerated loss of current biodiversity can have disastrous consequences on fundamental aspects of human societies and the global economy. Numerous agreements have been promoted and ratified by many countries due to the urgency of limiting environmental deterioration. Colombia is a pioneer in the formulation of environmental legislation in the world. Through the analysis of different conservation plans of fauna species, some similarities were found in regard to goals, evaluation methods, action strategies, but above all many challenges facing the regional and global responsibility of our country as a bastion of mega diversity